2013
DOI: 10.3390/agronomy3030524
|View full text |Cite
|
Sign up to set email alerts
|

Large Genetic Variability in Chickpea for Tolerance to Herbicides Imazethapyr and Metribuzin

Abstract: Chickpea (Cicer arietinum L.) is known to be sensitive to many herbicides and, therefore, choices for using post-emergence herbicides for weed control are limited. The present study was aimed at identifying sources of tolerance to two herbicides with different modes of action (imazethapyr—amino acid synthesis inhibitor; and metribuzin—photosynthesis inhibitor) for use in breeding herbicide tolerant cultivars. Screening of 300 diverse chickpea genotypes (278 accessions from the reference set and 22 breeding lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 25 publications
9
38
0
Order By: Relevance
“…In present day, when farm labourers are becoming expansive day by day, the farmers are demanding chickpea varieties with traits such as suitability to mechanical harvesting and toler-ance to herbicides to enhance mechanization of chickpea cultivation Gaur et al 2012a ). Large genetic variations have been observed for postemergence herbicide tolerance in chickpea (Gaur et al 2013a ) which can be utilized for the development of herbicide-tolerant cultivars. Several diseases, such as dry root rot, collar rot, wet root rot and stem rot, were minor hitherto and are becoming potential threat to chickpea cultivation in many parts of the world including India.…”
Section: Traits Of Importance For Base Broadeningmentioning
confidence: 99%
“…In present day, when farm labourers are becoming expansive day by day, the farmers are demanding chickpea varieties with traits such as suitability to mechanical harvesting and toler-ance to herbicides to enhance mechanization of chickpea cultivation Gaur et al 2012a ). Large genetic variations have been observed for postemergence herbicide tolerance in chickpea (Gaur et al 2013a ) which can be utilized for the development of herbicide-tolerant cultivars. Several diseases, such as dry root rot, collar rot, wet root rot and stem rot, were minor hitherto and are becoming potential threat to chickpea cultivation in many parts of the world including India.…”
Section: Traits Of Importance For Base Broadeningmentioning
confidence: 99%
“…Visual scoring for herbicide tolerance was done 10, 20 and 30 days after spray. Gaur et al (2013) reported that new flushes start to come after 25 days of spray, therefore, one scoring should be done after 25 days to take into account plants which have recovered fast. Taran et al (2010) scored the plant injury in greenhouse condition at 7, 14 and 21 days after spray.…”
Section: Preliminary Screening Of Genotypes For Herbicide Tolerancementioning
confidence: 99%
“…Zhou et al (2007) reported that resistance to AHAS inhibiting herbicide results from altered sequences of AHAS encoding genes leading to production of altered AHAS having tolerance to herbicide. Gaur et al (2013) reported that imazethapyr mainly killed the meristematic tips of branches resulting in elongation of branches, needle shaped leaves, delayed flowering, deformation of flowers and bud, poor pod setting and reduction in pod and seed size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier research has shown the potential of graminicides (fluazifop, fenoxaprop and quizalofop) for controlling weeds of the Poaceae family with no adverse effect on the chickpea (Plew et al, 1994;Malik et al, 2001;Khan et al, 2018;Nath et al, 2018); of fomesafen and acifluorfen for the control of broadleaf weeds, even when causing visual lesions at the start of chickpea development (Malik et al, 2001;Boydston et al, 2017;Nath et al, 2018); while the potential of the herbicides imazethapyr, imazamox and metribuzin depends strongly on the correct choice of genotype, a poorly managed trait can compromise yield in areas of chickpea cultivation (Tar'an et al, 2010;Tar'an et al, 2013;Jain & Tar'an, 2013;Gaur et al, 2013;Jefferies et al, 2016).…”
Section: Introductionmentioning
confidence: 99%